Anthropometric Study on Hand Length and Breadth of Male Laundry Ironing Professionals Working at the Northern Part of Dhaka Metropolitan City (Bangladesh Journal of Anatomy, 2017)
Context: “Fitting the person to the task” is a modern day ergonomic principle. This shift of paradigm emphasizes on a match between the requirements of the task and the physical and mental capabilities of the people performing the task. Since the industrial revolution, ergonomic concepts have become even more pertinent to the health, safety and productivity of the workers as interaction between man and machine is increasing day by day. The present study primarily aimed at generating a baseline data on hand length and breadth of the Bangladeshi population. Comparisons between the right and left hands of the present study group as well as between the results of the present work with the findings of other nationals were also done to see whether these two dimensions vary in respect to handedness and nationality. Taking account of such variations is crucial in designing of hand tools and workspaces for a particular population. Materials and method: This is a cross sectional analytical study conducted at the Department of Anatomy, Dhaka Medical College, Dhaka from July 2013 to June 2014. The study was carried out on 100 righthanded male laundry ironing professionals working at the Northern part of Dhaka Metropolitan City. The subjects were selected purposively. Results: Findings of the present study indicate that the right hand breadth varies significantly from the left hand breadth in the laundry ironing professionals working at the Northern part of Dhaka Metropolitan City whereas no significant difference in hand length is observed between the right and left sides of the same population. It is also noted that significant differences in hand length and breadth exist between the subjects of the present study and the subjects of other countries. Conclusion: This article highlights the differences in anthropometric dimensions between the right and left hand of the same study group of Bangladeshi population as well as between the study groups of different nationalities. The data gathered here can hopefully be utilized as a reference pool in ergonomic designing of hand tools, workstations and layout designs unique for Bangladeshi workers.Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 2 , pp. 67-72